1995
DOI: 10.1116/1.588002
|View full text |Cite
|
Sign up to set email alerts
|

Postgrowth of a Si contact layer on an air-exposed Si1−xGex/Si single quantum well grown by gas-source molecular beam epitaxy, for use in an electroluminescent device

Abstract: A Si contact layer for an electroluminescent (EL) diode was successfully grown on a Si1−xGex/Si single quantum well (SQW) layer by ‘‘hybrid’’ Si molecular beam epitaxy (MBE). The ‘‘hybrid’’ MBE was performed by growing the Si contact layer in a solid-source MBE chamber after transferring the sample through air from a gas-source MBE (GSMBE) chamber in which the starting SQW layer was initially grown by using disilane (Si2H6) and germane (GeH4). The growth characteristics of the hybrid MBE were investigated by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 17 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Continued progress in materials quality and device design has resulted in improvements in EL device performance (see, for example, Refs. (82)(83)(84)(85)(86)) to the point that room temperature EL has since been reported at wavelengths near 1.3 µm (82,86). The major problem with such devices for practical purposes at present is their low efficiency at room temperature, which is again due to exciton thermal dissociation (82,86).…”
Section: Band Structure Engineering Via Alloyingmentioning
confidence: 99%
“…Continued progress in materials quality and device design has resulted in improvements in EL device performance (see, for example, Refs. (82)(83)(84)(85)(86)) to the point that room temperature EL has since been reported at wavelengths near 1.3 µm (82,86). The major problem with such devices for practical purposes at present is their low efficiency at room temperature, which is again due to exciton thermal dissociation (82,86).…”
Section: Band Structure Engineering Via Alloyingmentioning
confidence: 99%
“…In early work, it was found that the EL from Si1−xGex/Si p-i-n diodes was quenched when the temperature was increased above 80 K , but EL was later reported at higher temperatures (up to 220 K) in p-i-n diode structures (Robbins et al, 1991). There has been a continual improvement in materials quality and this, coupled with changes in device design, has continued to advance EL device performance [see, for example, Fukatsu et al (1992), Mi et al (1992), Kato et al (1995), Förster et al (1996), and Presting et al (1996)] to the point that EL has been obtained at wavelengths near 1.3 μm at room temperature (Mi et al, 1992;Presting et al, 1996). From a practical point of view, one major problem with such devices at present is their low efficiency at room temperature, which results from thermal dissociation of the exciton (Mi et al, 1992;Presting et al, 1996).…”
Section: Band Structure Engineering Via Alloyingmentioning
confidence: 99%